The impact of the American withdrawal on Iraqi national security - Dr.Ali Muzahim Mujbil (The college of law and political science journal, 2024)
After the year 2003 AD, Iraq witnessed a distinct situation that emerged from a phase of almost complete absence of a state, then a decline in the fabric of a state with which the Iraqis or Iraq’s influential neighbors disagreed with it structurally, which made them mention it. Their contradictions in the new constitution, and the most difficult of the above, the United States of America, which is supposed to sponsor the new building, has begun to find an exit mechanism, and its strength comes from this new building. This was evident when a security agreement was concluded in late 2011 withdrawing its forces from Iraq.